In situ variable-temperature single crystal X-ray diffraction studies of the single-crystal-to-single-crystal dehydration and rehydration of a mixed-ligand 2D zinc metal–organic framework using trimesate and 4, 4′-bipyridine-N, N′-dioxide as ligands. Issue 46 (14th September 2015) - Tahier, Tayyibah; Oliver, Clive L.
Abstract : A mixed-ligand 2D MOF based on ZnSO4, trimesate and 4, 4′-bipyridine- N, N ′-dioxide shows reversible loss of uncoordinated and coordinated water molecules. Abstract : A mixed-ligand 2D MOF based on ZnSO4, trimesate and 4, 4′-bipyridine- N, N ′-dioxide was synthesized and characterized by variable-temperature X-ray diffraction, thermal analysis and infrared spectroscopy. It is the first crystal structure, let alone coordination polymer, containing both trimesate (or trimesic acid) and 4, 4′-bipyridine- N, N ′-dioxide. The 2D layers are arranged in a polar fashion with adjacent layers creating isolated cavities. Single crystal structure analyses of the same crystal at different temperatures confirm that dehydration occurs via a single-crystal-to-single-crystal transformation and yield insight into the order of water release upon dehydration. Rehydration of the 2D MOF occurred when exposed to air which was confirmed by thermogravimetric analysis and single crystal X-ray diffraction. Water vapour sorption experiments show a type I isotherm, typical of microporous materials.